Pengembangan Model Pembelajaran CO PjBL Untuk Meningkatkan Kemampuan Berfikir Kritis dan Pemecahan Masalah Mahasiswa Jurusan Geografi Angkatan Tahun 2023 Pada Mata Kuliah Kartografi - Sanjaya, Amir; Yusuf, Muhammad; Maru, Rosmini; Nyompa, ukri; H, Hasriyanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this study was to find out how the learning model development results from the blend between PjBL and Concep Based Learning models and how effective the resulting learning models are. The research method used is qualitative descriptive, In this research method the researcher will try to give systematically and carefully regarding the actual facts as well as the nature of the particular population. As the name suggests, then the mode of delivery is in descriptive form. The population in this study was 2023 batch geography major students totaling 30 people. The data collection techniques used are generalizations consisting of objects having certain quantities and characteristics that the researcher has applied to study and then draw final conclusions.